Enhanced photoelectrochemical characteristic of TiO2 nanotubes via surface plasma treatment. Issue 21 (1st November 2021) - Han, HyukSu; Moon, Sung-I; Choi, Seunggun; Enkhtuvshin, Enkhbayar; Kim, So Jung; Jung, Sun Young; Thu Thao, Nguyen Thi; Song, Taeseup
Abstract: Photoelectrochemical (PEC) water splitting is one of promising green method to generated renewable energy such as hydrogen. To realize PEC for hydrogen production, it is indispensable to develop a high-performance photocatalyst. In this study, a facile surface engineering using plasma treatment is developed for TiO2 nanotubes where the surface becomes porous and partially amorphized resulting in the enhanced photocatalytic activity. Moreover, electronic configuration of TiO2 nanotubes were effectively modulated via ion plasma treatment, which improves charge transport and light-absorption in TiO2 nanotubes. Electronic modulations in combination with the intriguing nanoporous structure after ion plasma treatment leads to significantly enhanced photocatalytic activity of TiO2 nanotubes, which can be applied for designing next high-performance photocatalysts. Graphical abstract: A significance enhancement of photoelectrochemical water oxidation in alkaline solution is achieved for TiO2 nanotube arrays via a facile surface plasma treatment. Image 1 Highlights: The ion plasma treatment can induce nanoporous surface structure of TiO2 nanotube. TiO2 nanotubes after ion plasma treatment efficiently absorb visible light due to the modified electronic configuration. Electronic and structural changes of TiO2 nanotubes via ion plasma treatment can boost photocatalytic activity.